Effect of temperature on carbon accumulation in northern lake systems over the past 21,000 years - Pfalz, Gregor; Diekmann, Bernhard; Freytag, Johann-Christoph; Biskaborn, Boris K. (Frontiers in Earth Science, 2023)
Rising industrial emissions of carbon dioxide and methane highlight the important role of carbon sinks and sources in fast-changing northern landscapes. Northern lake systems play a key role in regulating organic carbon input by accumulating carbon in their sediment. Here we look at the lake history of 28 lakes (between 50° N to 80° N) over the past 21 000 years to explore the relationship between carbon accumulation in lakes and temperature changes. For this study, we calculated organic carbon accumulation rates (OCAR) using measured and newly generated organic carbon and dry bulk density data. To estimate new data, we used and evaluated seven different regression techniques in addition to a log-linear model as our base model. We also used combined age-depth modeling to derive sedimentation rates and the TraCE-21ka climate reanalysis dataset to understand temperature development since the Last Glacial Maximum. We determined correlation between temperature and OCAR by using four different correlation coefficients. In our data collection, we found a slightly positive association between OCAR and temperature. OCAR values peaked during warm periods Bølling Allerød (38.07 g m -² yr -1 ) and the Early Holocene (40.68 g m -² yr -1 ), while lowest values occurred during the cold phases of Last Glacial Maximum (9.47 g m-² yr-1) and Last Deglaciation (10.53 g m-² yr-1). However, high temperatures did not directly lead to high OCAR values. We assume that rapid warming events lead to high carbon accumulation in lakes, but as warming progresses, this effect appears to change as increased microbial activity triggers greater outgassing. Despite the complexity of environmental forcing mechanisms affecting individual lake systems, our study showed statistical significance between measured OCAR and modelled paleotemperature for 11 out of 28 lakes. We concluded that air temperature alone appears to drive the carbon accumulation in lakes. We expected that other factors (catchment vegetation, permafrost, and lake characteristics) would influence accumulation rates, but could not discover a conclusive factor that had a statistical significant impact. More data available on long-term records from northern lake systems could lead to more confidence and accuracy on the matter.